Analysis of categorical data : dual scaling and its applications - Nishisato, Shizuhiko, 1935- (Mathematical expositions, 2018)
This volume presents a unified and up-to-date account of the theory and methods of applying one of the most useful and widely applicable techniques of data analysis, 'dual scaling.' It addresses issues of interest to a wide variety of researchers concerned with data that are categorical in nature or by design: in the life sciences, the social sciences, and statistics.